Soda-Anthraquinone-Catalyzed Delignification of Coconut Husk Waste - Eka Fitriani Ahmad; Puji Lestari; Katharina Oginawati; Yoki Yulizar; Julinton Sianturi; Muhammad Miftahul Munir; Adawiah Adawiah (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2026)
This study investigates the role of anthraquinone (AQ) in decomposing coconut husk waste, specifically collected from Banten, to produce pure α-cellulose pulp. The process used sodium hydroxide (NaOH) at 10%, 15%, and 20% concentrations, with 0.1 g of AQ added as a catalyst, and a waste-to-liquid ratio of 1:8 throughout. The goal is to accelerate lignin degradation while protecting cellulose in the material, thereby yielding higher-quality pulp. The Banten coconut husk analysis showed an α-cellulose content of 30.38%. Higher NaOH concentrations reduced pulp yield but increased lignin removal, indicated by lower kappa numbers. AQ addition enhanced lignin removal and preserved cellulose compared to the absence of AQ. The optimal outcome was achieved with 15% NaOH and 0.1 g AQ, balancing lignin removal and cellulose preservation. These findings indicate that anthraquinone can support sustainable pulp production from agricultural waste. Copyright © 2026 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).